2022
DOI: 10.2174/1871520622666220318090147
|View full text |Cite
|
Sign up to set email alerts
|

Azole-Pyrimidine Hybrid Anticancer Agents: A Review of Molecular Structure, Structure Activity Relationship, and Molecular Docking

Abstract: Cancer has emerged as one of the leading causes of deaths globally partly due to the steady rise in anticancer drug resistance. Pyrimidine and pyrimidine-fused heterocycles are some of the privileged scaffolds in medicine, as they possess diverse biological properties. Pyrimidines containing azole nucleus possesses inestimable anticancer potency and has enormous potential to conduct the regulation of cellular pathways for selective anticancer activity. The present review outlines the molecular structure of py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Molecular docking is the most popular computational structure-based drug design method and has become an effective computer-aided technique for drug discovery [ 55 , 56 , 57 ]. The spatial and energetic match allows molecular docking to predict the conformation of small molecule ligands in the appropriate target binding site with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking is the most popular computational structure-based drug design method and has become an effective computer-aided technique for drug discovery [ 55 , 56 , 57 ]. The spatial and energetic match allows molecular docking to predict the conformation of small molecule ligands in the appropriate target binding site with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, further incorporation of a 5-nitrothien-2-yl moiety (15) resulted in the slight loss of anticancer activity (47.7%) (p < 0.001). The incorporation of an aminoacetophenone substitution (16) resulted in decreased anticancer activity (65.1%) (p < 0.001), while the addition of a 2-oxoindolin-3-ylidene fragment (17) resulted in strikingly enhanced anticancer activity (26.2%) (Figure 1).…”
Section: Novel 1-(2-hydroxyphenyl)-5-oxopyrrolidine-3-carboxylic Acid...mentioning
confidence: 99%
“…Diversely functionalized azole analogues are considered to be one of the most important frameworks for the development of numerous pharmacologically active compounds with antifungal, antibacterial, antidiabetic, and anticancer activities [10][11][12][13][14][15][16][17][18]. Interestingly, several studies have shown that azole derivatives containing naphthalene show selective and Gram-positive-bacteria-directed antimicrobial activity [19].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Azole moieties are a type of synthetic chemical molecule that is not found in nature. 5 Tetrazoles, which were first synthesized by J. A. Bladin in 1885, are made of a doubly unsaturated five-membered ring containing four nitrogen atoms and one carbon atom, known as the greatest quantity of nitrogen that may be found in a stable heterocyclic ring.…”
Section: Introductionmentioning
confidence: 99%